(untitled) (PerCursos, 2021)
This essay-style text analyzes the ways in which, between the mid-1920s and the mid-1960s, ways of defining the “being” of Brazilian culture were outlined, notably based on the interpretive effort of some selected intellectuals. To this end, it discusses perspectives regarding Brazil’s identity launched by intellectuals such as Gilberto Freyre, Sérgio Buarque de Holanda, Alcântara Machado, Mário de Andrade, Oswald de Andrade and Ariano Suassuna. Specifically, it observes the ways in which, in the intellectual scenario, the perspectives of modernism proposed by the São Paulo and Pernambuco groups that, in this scenario, disputed the protagonism in the process were opposed. Empirically, hemerographic materials, literary production and period cultural essays were used. In terms of historiographic references, authors such as Manoel Luiz Salgado Guimarães, Renato Ortiz, Mônica Pimenta Velloso and Eric Hobsbawm were used.